2018
DOI: 10.1111/jace.16061
|View full text |Cite
|
Sign up to set email alerts
|

The effects of external fields in ceramic sintering

Abstract: Field‐assisted processing techniques can enhance the kinetics of powder synthesis, accelerate sintering processes, and drive phase transformations at significantly lower temperatures compared to conventional methods. However, the exact nature of this nonthermal interaction between field and matter remains vastly speculative. A 2‐day workshop on “Electromagnetic Effects in Materials Synthesis” was organized at Carnegie Mellon University (Pittsburgh, USA) in June 2017, jointly sponsored by the U.S. National Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 214 publications
(339 reference statements)
0
26
0
Order By: Relevance
“…The property of a material depends on its processing parameters, such as heating schedule (or heat treatment), hold time, and processing environment. Recently, externally applied fields such as direct electric fields and electromagnetic (EM) fields have been used to reduce the time and temperature requirements for material processing . In addition to saving time and energy, applied fields can also affect material properties by inducing phase transformations or altering microstructure and morphologies of nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…The property of a material depends on its processing parameters, such as heating schedule (or heat treatment), hold time, and processing environment. Recently, externally applied fields such as direct electric fields and electromagnetic (EM) fields have been used to reduce the time and temperature requirements for material processing . In addition to saving time and energy, applied fields can also affect material properties by inducing phase transformations or altering microstructure and morphologies of nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…To realize this potential, it is critical to address open questions in the community surrounding the underlying mechanisms of MWR and field-assisted synthesis methods. 10,23 Many of the synchrotron-based characterization tools presented above provide valuable insight into these mechanisms, but there is still no clear consensus regarding how EM fields promote these rapid, low-temperature processes. For example, is the rapid rate enhancement driven purely by enhanced heating rates or more efficient volumetric heating, or can applied fields influence mass transport or defect generation in ways not possible via thermal mechanisms alone?…”
Section: Summary and Future Outlookmentioning
confidence: 99%
“…As discussed previously, many of the proposed thermal and non-thermal mechanisms, such as rapid heating rates, localized heating, and potential fieldinduced defect generation, are consistent across both MWR-assisted synthesis and E-field-assisted sintering (e.g., flash sintering). 10,23 In particular, in situ synchrotron-based studies of flash sintering in ceramic oxides have been useful in identifying potential nonthermal effects of E-field exposure, such as field-induced texture, 39 non-thermal anisotropic lattice expansion, 53 formation of field-stabilized phases, 54 and increased disorder on the oxygen sublattice relative to the cation sublattice. 55 These observations, particularly with regard to field-mediated texture, phase formation, and oxygen defects, appear to have a high degree of similarity to the observed experimental results on MWR-assisted synthesis presented in this review.…”
Section: Summary and Future Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in situ synchrotron studies 9 have observed metastable phase transformations 10,11 and abnormal lattice expansions across the sample 12,13 during flash sintering. Microstructure characterization after flash sintering revealed asymmetric grain growth, [14][15][16] texturing, 3,17 and high density of defects, 3,17,18 as a result of the generation and mobility of the charged species caused by the applied DC field.…”
Section: Introductionmentioning
confidence: 99%